PENGARUH KETERLIBATAN KARYAWAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Munfaridi Munfaridi; A. Jalaludin Sayuti (Politeknik Negeri Sriwijaya, 2020)
Engagement of employee is an interesting concept to study in relation to other concepts that support the success of an organization. This study is based on a quantitative method approach using path analysis to illustrate the relationships between concepts. The research sample is a travel agency employee in Palembang by determining the sample using a purposive sampling technique. The study explained that the relationship between employee involvement with employee satisfaction was stated to have no significant effect. The relationship between employee involvement with employee performance is stated to have no significant effect. Then, the relationship between employee satisfaction with employee performance is stated to have a significant effect. Study outcomes are expected to contribute to the management of travel agents in managing employees.